RASIO KONTRIBUSI PAJAK PENERANGAN JALAN DAN PAJAK HIBURAN TERHADAP PENDAPATAN ASLI DAERAH (PAD) KOTA BANDUNG - Reza Kurniawan; Endang Susilawati (Jurnal Akuntansi Bisnis dan Ekonomi, 2021)
The purpose of this study was to determine the effect of Street Lighting Tax and Entertainment Tax on Bandung Regional Original Income partially and simultaneously. The study was conducted at Badan Pengelolaan Keuangan dan Aset (BPKA) of Bandung city. The analytical method used is a descriptive method that analyzes data on the realization of the Street Lighting Tax and Entertainment Tax in 2013-2019. The t-test results (partial) show that partially the Street Lighting Tax and Entertainment Tax have no influence on the Regional Original Income, while the F test results that simultaneously the Street Lighting Tax and the Entertainment Tax have an influence on the Regional Original Income.